Videoconference Interviews for Admission to a Pediatric Residency Program during the COVID-19 Pandemic: Candidates’ Perspectives - A. Bahaidarah, Saud (Journal of King Abdulaziz University: Medical Sciences, 2021)
With the emergence of Covid-19 pandemic, understanding the effectiveness of videoconference interviews as an alternative to face- to-face interviews in the research process has become necessary. This study investigated the effectiveness of videoconference interviews, adopted due to the COVID-19 pandemic, in the selection process for a pediatric residency program from candidates’ perspectives. The Zoom videoconferencing application was used for online interviews with all candidates. A post-interview questionnaire survey developed using Google Forms was conducted through email to identify their perspectives on the various aspects of the videoconference interview method, including communication, convenience, and interview-related stress. Most participants found videoconference interviews using the Zoom application accessible and convenient and reported that both verbal and nonverbal communications were clear. The videoconferencing format and the pre-interview meeting with the Residency Training Program director were reported to reduce interview-related stress. Most participants considered videoconferencing a suitable substitute for face-to-face interviews. Major obstacles were related to internet connection speed, the time limit on the free version of the Zoom application and securing a quiet environment conducive to interviews. So, videoconference interviews are an effective alternative to face-to-face interviews from the candidates’ perspectives. Internet speed connection and interview environment play an important role in conducting interviews. A meeting platform should ensure high bandwidth, synchronicity, privacy, and security. Future studies should consider interviewers’ perspectives on videoconference interviews.